2020
DOI: 10.1093/jme/tjaa235
|View full text |Cite
|
Sign up to set email alerts
|

Field Competitiveness of Aedes albopictus (Diptera: Culicidae) Irradiated Males in Pilot Sterile Insect Technique Trials in Northern Italy

Abstract: Vector-borne diseases account for 17% of infectious diseases, leading to more than one million deaths each year. Mosquitoes are responsible for 90% of the casualties and alternative control methods to insecticides are urgently needed, especially against Aedes vectors. Aedes albopictus is a particularly important species, causing major public health problems because it is a vector of several arboviruses and has a strong invasive behavior. Various genetic control methods have been proposed to be integrated into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 31 publications
2
37
0
1
Order By: Relevance
“…From a performance perspective, producing better quality sterile males can lead to the release of more competitive insects in the field. This aspect can be very useful, as it could result in a smaller number of released males, thus reducing production costs [ 14 , 15 ]. The achievement of this objective could be facilitated by the standardization and improvement of the rearing conditions, including the optimization of the larval medium.…”
Section: Introductionmentioning
confidence: 99%
“…From a performance perspective, producing better quality sterile males can lead to the release of more competitive insects in the field. This aspect can be very useful, as it could result in a smaller number of released males, thus reducing production costs [ 14 , 15 ]. The achievement of this objective could be facilitated by the standardization and improvement of the rearing conditions, including the optimization of the larval medium.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported a strong negative correlation between the field competitiveness of the Ae. albopictus males released and the ratio of sterile to wild males [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…aegypti per trap (eggs/trap) were averaged per time unit (week). The percentage of induced egg sterility was calculated by Equation (1), proposed by Bellini et al [ 29 , 30 ]. S = 1 − ((Eh I /E I ) (E C /Eh C )) where S is the percent egg sterility, Eh is the mean number of hatched egg per ovitrap per week, E is the mean number of eggs per trap per week, I is the intervention area and C is the control area.…”
Section: Methodsmentioning
confidence: 99%
“…aegypti per trap (eggs/ trap) were averaged per time unit (week). The induced egg sterility percentage was calculated by the Equation (1), proposed by Bellini et al [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported strong negative correlation between the field competitiveness of the Ae. albopictus males released and the ratio of sterile to wild males [29].…”
Section: Discussionmentioning
confidence: 99%